2018
DOI: 10.1002/adhm.201800186
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Enzymatically Cross‐Linked Silk Fibroin Tubular Conduits for Guided Tissue Regeneration

Abstract: Hollow tubular conduits (TCs) with tunable architecture and biological properties are in great need for modulating cell functions and drug delivery in guided tissue regeneration. Here, a new methodology to produce enzymatically cross-linked silk fibroin TCs is described, which takes advantage of the tyrosine groups present in silk structure that are known to allow the formation of a covalently cross-linked hydrogel. Three different processing methods are used as a final step to modulate the properties of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 71 publications
1
47
0
Order By: Relevance
“…Such characteristic must be previously tested and avoided at all costs, since calcification of a conduit would hinder regeneration in a great extent. In fact, Carvalho et al [71] recently reported on a silk fibroin NGC that would or not calcify, according to the method of solvent removal and final surface properties.…”
Section: Strategies For Nerve Repairmentioning
confidence: 99%
See 2 more Smart Citations
“…Such characteristic must be previously tested and avoided at all costs, since calcification of a conduit would hinder regeneration in a great extent. In fact, Carvalho et al [71] recently reported on a silk fibroin NGC that would or not calcify, according to the method of solvent removal and final surface properties.…”
Section: Strategies For Nerve Repairmentioning
confidence: 99%
“…Carvalho et al [71] produced tunable enzymatically cross-linked SF NGCs, resourcing to tyrosine groups present in silk structure that are known for allowing the formation of a covalently cross-linked hydrogel. The fact that the process involves an enzymatic crosslinking allows tuning several parameters in the final conduit, i.e.…”
Section: Silk Fibroinmentioning
confidence: 99%
See 1 more Smart Citation
“…16,52 An ideal NGC or PNW intended for PNR needs to feature a combination of optimal material, size, architecture and surface properties to be fully effective. 53 These features must allow the formation of a new ECM, consisting of endothelial cells, and subsequently blood vessels, Schwann cells and the correct type and amount of fibroblasts, which will collectively create favourable circumstances for nerve regeneration to occur. 54 In this study, we propose the use of solvent cast CHT/ keratin membranes as possible tools to aid in the repair of damaged nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Various microfabrication techniques for tissue engineering, such as electrospinning [ 14 , 15 , 16 , 17 , 18 , 19 ], cell-sheet engineering [ 20 , 21 , 22 ], and mold-casting [ 23 , 24 , 25 , 26 ], have been widely studied to make complex multi-layered architecture for artificial functional tubular tissues. These approaches would use additional substrates (e.g., rotating rod, sacrificial mold) to create the tubular architecture, as well as requiring complex and multiple manufacturing processes.…”
Section: Introductionmentioning
confidence: 99%